Case Report: Visual Rehabilitation in Hemianopia Patients. Home-Based Visual Rehabilitation in Patients With Hemianopia Consecutive to Brain Tumor Treatment: Feasibility and Potential Effectiveness - Daibert-Nido, Monica; Pyatova, Yulia; Cheung, Kyle; Nayomi, Camilus; Markowitz, Samuel N.; Bouffet, Eric; Reber, Michael (Frontiers in Neurology, 2021)
Background/Objectives: Visual field loss is frequent in patient with brain tumors, worsening their daily life, exacerbating the burden of disease and no supportive care strategies exist. In this case series we sought to characterize the feasibility and potential effectiveness of a home-based visual rehabilitation program in hemianopia patients using immersive virtual-reality stimulation. Subjects/Methods: Two patients, one with homonymous hemianopia and the other with bitemporal hemianopia, consecutive to pediatric brain tumors, with no prior visual rehabilitation performed fifteen minutes of home-based audiovisual stimulation every 2 days for 6 weeks (case 2) and 7 weeks (case 1) between February and August 2020. Patients used a virtual-reality, stand-alone and remotely controlled device loaded with a non-commercial audiovisual stimulation program managed in real-time from the laboratory. Standard visual outcomes assessed in usual care in visual rehabilitation were measured at the clinic. Following a mixed method approach in this pragmatic study of 2 cases, we collected quantitative and qualitative data on feasibility and potential effectiveness and compared the results pre- and post-treatment. Results: Implementation and wireless delivery of the audiovisual stimulation, remote data collection and analysis for case 1 and 2 who completed respectively 19/20 and 20/20 audiovisual stimulation sessions at home, altogether indicated feasibility. Contrast sensitivity increased in both eyes for case 1 and 2. Visual fields, measured by binocular Esterman and monocular Humphrey full field analyses, improved in case 1. A minor increase was observed in case 2. Case 1 and 2 enhanced reading speed. Case 2 strongly improved quality of life scores. Conclusion: This is the first report of a home-based virtual-reality visual rehabilitation program for adult patients with hemianopia consecutive to a pediatric brain tumor. We show the feasibility in real-world conditions and potential effectiveness of such technology on visual perception and quality of life.